2008
DOI: 10.2527/jas.2008-1122
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of human chorionic gonadotropin as a replacement for gonadotropin-releasing hormone in ovulation-synchronization protocols before fixed timed artificial insemination in beef cattle1

Abstract: Two experiments were conducted during 2 yr to evaluate differences in ovulation potential and fertility in response to GnRH or hCG. In Exp. 1, 46 beef cows were given 100 microg of GnRH or 500, 1,000, 2,000, or 3,000 IU of hCG. Ovulation incidence was not different between GnRH and any of the hCG doses, indicating that ovulatory capacity of at least 500 IU of hCG was equivalent to GnRH. In Exp. 2, beef cows (n = 676) at 6 locations were assigned randomly to a 2 x 3 factorial arrangement of treatments. Main eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 20 publications
2
9
3
Order By: Relevance
“…Our results agree with data reported by researchers [17] who induced ovulation in women, beef cows [30], and dairy heifers [32] treated with hCG injections. In addition, our data is also in line with research findings which suggest that hCG selectively stimulates folliculogenesis and induces ovulation in women [33].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results agree with data reported by researchers [17] who induced ovulation in women, beef cows [30], and dairy heifers [32] treated with hCG injections. In addition, our data is also in line with research findings which suggest that hCG selectively stimulates folliculogenesis and induces ovulation in women [33].…”
Section: Discussionsupporting
confidence: 93%
“…These investigators concluded that progesterone reduced the ability of endogenous or exogenous estradiol to induce a preovulatory LH surge and ovulation. Furthermore, other investigators reported that cows with progesterone concentrations greater than 1 ng/ml before treatment with either hCG or GnRH tend to ovulate less often than those having progesterone levels below 1 ng/ml [30]. Nevertheless, the group receiving the PGF + GnRH + hCG treatment in the present study ovulated earlier than the other two experimental groups even though progesterone levels were higher (3.78 ± 1.34) than 1 ng/ml.…”
Section: Discussioncontrasting
confidence: 49%
“…The capacity of hCG to induce ovulation of small follicles has been reported (Burns et al, 2008;Stevenson et al, 2008b). Ovulation of small follicles may result in poorer fertility possibly because of a resulting smaller CL with a decreased capacity to produce P4 (Vasconcelos et al, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…When hCG was administered to beef cows, CL development resulted from follicles <10 mm in diameter (Sheffel et al, 1982) and 6 of 18 Iactating dairy cows treated with hCG having follicles <10 mm in diameter ovulated compared with 0 of 13 treated with GnRH (Buttrey et al, 2010). In addition, beef cows receiving 1,000 IU of hCG tended to have greater concentrations of progesterone (P4) 7 d after treatment than those receiving GnRH (Burns et al, 2008). Thus, hCG may have greater capacity to luteinize preovulatory follicles compared with GnRH (Schmitt et al, 1996b).…”
Section: Introductionmentioning
confidence: 95%
“…No difference in the nature of the treatment (hCG or GnRH) was observed. The GnRH and hCG treatments have similar effects on the ovary (Fricke et al, 1993), induction of ovulation (Burns et al, 2008), and formation of accessory CL (Schmitt et al, 1996b).…”
Section: )mentioning
confidence: 89%